A novel stage-specific glycosomal nucleoside diphosphate kinase from Trypanosoma cruzi - Camara, María de los Milagros (2017)
Nucleoside diphosphate kinases (NDPK) are key enzymes involved in the intracellular nucleotide maintenance in all living organisms, especially in trypanosomatids which are unable to synthesise purines de novo. Four putative NDPK isoforms were identified in the Trypanosoma cruzi Chagas, 1909 genome but only two of them were characterised so far. In this work, we studied a novel isoform from T. cruzi called TcNDPK3. This enzyme presents an atypical N-terminal extension similar to the DM10 domains. In T. cruzi, DM10 sequences targeted other NDPK isoform (TcNDPK2) to the cytoskeleton, but TcNDPK3 was localised in glycosomes despite lacking a typical peroxisomal targeting signal. In addition, TcNDPK3 was found only in the bloodstream trypomastigotes where glycolytic enzymes are very abundant. However, TcNDPK3 mRNA was also detected at lower levels in amastigotes suggesting regulation at protein and mRNA level. Finally, 33 TcNDPK3 gene orthologs were identified in the available kinetoplastid genomes. The characterisation of new glycosomal enzymes provides novel targets for drug development to use in therapies of trypanosomatid associated diseases.